PELATIHAN KODEFIKASI KASUS OBSTETRIC BERDASARKAN ICD 10 DI RSIA CICIK PADANG - Nurul Fitri Khumaira; Yastori Yastori (LPPM Universitas Bina Bangsa, 2024)
Obstetric coding issues are an important problem in Mother and Child Hospitals. One of them is poor quality of coder in determining correct and complete codes, especially obstetric cases. Therefore, efforts are needed to improve coders capabilities of coding obstetric cases. One of the capability improvements that can be carried out is training related to coding obstetric cases, such as Socialization and Practice about obstetric cases. This community service activity was held on Tuesday, May 28 2024 at RSIA Cicik Padang by 5 Medical Record Officers. Evaluation of this activity is a pretest and posttest with the same questions. The average pretest score was 45 of 100 points. Meanwhile, the Posttest was 75 of 100 points. Based on these results, it can be concluded that Training is going very well and is increasing the ability and independence of coders to coding obstetric cases based on ICD X